ANALISIS PENGENDALIAN PIUTANG TERHADAP RISIKO PIUTANG TAK TERTAGIH PADA PT EXPRAVET NASUBA MEDAN - Adinda, Reza; Junaidi, Listya Devi (Worksheet : Jurnal Akuntansi, 2023)
This research aims to find out and analyze how receivables control is implemented on the risk of bad debts at PT Expravet Nasuba Medan. The research method uses a qualitative approach with descriptive research methods. The data used is primary data, namely data obtained directly from the leadership and employees related to the problems studied at PT. Expravet Nasuba Medan. The data analysis technique used is descriptive analysis technique. The results of this research conclude that the control of receivables on the risk of bad debts at PT Expravet Nasuba Medan has not been carried out effectively, this can be seen from the data on bad debts based on the age of the receivables which shows that each year the bad debts experience a fairly high increase.Keyword: Receivables Control; Receivables Risk.